PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM SIKLUS PRODUKSI SEBAGAI PENENTUAN BIAYA PRODUKSI PADA UMKM MELIA CAKES - Nur Noviana, Tarissa; Nurodin, Idang; Martaseli, Evi (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
Based on the current phenomena, the UMKM does not correct for record and count production costs and is still not completely used in the production cost statement. This study aims to describe the production cost determined after the implementation of the Accounting Information System of Production CycleÂ database. A qualitative method was used, and the types of data used were observations, interviews, and documentation. The results of this study indicate that Melia Cakes business activity still used the manual of record and count production costs. The production cost was determined almost correctly by Melia Cakes, but there are still costs not included in the production cost. Therefore, implementation of the Accounting Information System of Production Cycle is required for business activity. Because the Accounting Information System makes it easier to count, record, and determine production costs, it also provides an effective and efficient control of production costs.